Pengembangan Usaha Geez Coffee Melalui Repackaging dan Collaboration - Gisti Khoerunisa; Rohandi, Moch. Malik Akbar; Mahani, Septiana Ayu Estri (UNISBA Press, 2024)
Abstract. In businesses that are businesses in the culinary field, especially in beverages that are widespread in Indonesia, West Java, especially the city of Bandung, the Cibiru area. There is a coffee processing business, namely Geez Coffee, which is unique in the type of coffee it chooses. The problems that occur in the business carried out by Geez Coffee itself are production, marketing, finance, venture capital. In managing this business, researchers also use various strategies such as the Business Model Canvas, SWOT analysis, Porter's Five Forces, Ansoff Matrix, Target and Performance, and the BCG Matrix to carry out business development. The result of this research is that it is necessary to find more capital to cover a wider market and maximize activities in making new products through repackaging, making financial reports, registering legality such as halal products and making HKI as one of the things related to running business activities. Abstrak. Pada usaha yang merupakan usaha di bidang kuliner terutama pada minuman yang tersebar luas di Indonesia, Jawa Barat, khususnya Kota Bandung daerah Cibiru. Terdapat usaha olahan kopi yaitu Geez Coffee yang memiliki keunikan pada jenis kopi yang dipilih. Permasalahan yang terjadi pada usaha yang dilakukan oleh Geez Coffee sendiri yaitu produksi, pemasaran, keuangan, modal usaha. Dalam mengelola usaha ini pula peneliti menggunakan berbagai strategi seperti Business Model Canvas, analisis SWOT, Five Forces Porter, Ansoff Matrix, Target and Performance, dan BCG Matrix untuk melakukan pengembangan usaha. Hasil dari penelitian ini adalah perlu mencari modal yang lebih untuk mencakup pasar lebih luas serta memaksimalkan kegiatan dalam pembuatan produk baru melalui repackaging, pembuatan laporan keuangan, pendaftaran legalitas seperti halal produk dan pembuatan HKI sebagai salah satu hal yang bersangkutan dengan kegiatan usaha yang dijalankan.